Hematological and nutritional parameters in apparently healthy elderly individuals - Schaan,Mariza D'Agord (2007)
A non-probabilistic study in an elderly free living community was performed. The first analysis was cross-sectional in design and the additional analysis, a case-control design. In the first analysis, 745 subjects were enrolled. Additional analyses, made in 46 apparently healthy elderly subjects (AHE) and 33 young adults (YA) included: clinical, hematological and biochemical analyses, 24-hours nutritional recall and diet frequency questionnaire. The AHE were selected using the Senieur test protocol. To avoid selection bias in the AHE sample, additional analysis comparing cultural, socioeconomic, and health variables were compared between AHE and non-selected elderly with same dysfunction or morbidity (DE). The prevalence of AHE was 6.17% (n=46) among whom 4.3% were anemic. There were no statistically differences in hematocrit, hemoglobin, leukocytes and vitamin B12 levels between AHE and YA groups. Mean values of MCV, RDW, eosinophils, folate and ferritin were higher in the AHE than the YA group. On the other hand, platelets were higher in the YA group. No statistically significant difference occurred between the AHE and DE groups when nutritional indicators were compared. The comparison between nutritional indicators of anemic and non-anemic apparently healthy elderly people showed statistically significant differences in vitamin B12 and protein intake, which were lower in the anemic elderly. The results suggest independent biological differences between hematological parameters of elderly and young individuals.